Preparation of SBA-15 extrudates: Evaluation of textural and mechanical properties - Chandrasekar, Govindasamy; Hartmann, Martin; Murugesan, Velayutham (Journal of Porous Materials, 2009)
SBA-15 powder (P) was shaped into cylindrical extrudates (Ex) by compounding with additives such as bentonite (binder), methylcellulose and tetraethylorthosilicate (TEOS). The extrudates of SBA-15 were characterized by XRD, N adsorption and thermogravimetric analysis. The orderly growth of SBA-15 is evident from the XRD patterns. The surface area and pore volume of SBA-15 (P) were around 884 m/g and 1.1 cm/g, respectively. The decrease in surface area and pore volume were observed for SBA-15 (Ex) in comparison to SBA-15 (P). This may be due to partial blocking of pore entry and surface coverage of additives during shaping of extrudates. The mechanical strength of SBA-15 (Ex) was examined by vertical crushing method. The effect of additives on the mechanical strength of SBA-15 (Ex) was examined by varying the composition. The results indicate linear increase of mechanical strength with increase in the content of bentonite and methylcellulose, but non-linear response with increase of TEOS and water. Compounding additives have been established to improve the mechanical strength of the extrudates. © 2008 Springer Science+Business Media, LLC.
Keywords: Binder; Extrudate; Mechanical strength; Powder; SBA-15